2004
DOI: 10.1210/en.2003-1196
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein-6 Transgenic Mice: Postnatal Growth, Brain Development, and Reproduction Abnormalities

Abstract: In biological fluids, IGFs bind to six distinct binding proteins (IGFBP-1 to -6). IGFBP-6 is of particular interest because it has been shown to inhibit proliferation in many cell types and to be synthesized in the central nervous system (CNS). It also has the strongest affinity for IGF-II among the IGFBPs. To study IGFBP-6 function in vivo, we established IGFBP-6 transgenic mice in which human IGFBP-6 (hIGFBP-6) cDNA is expressed under the control of the glial fibrillary acidic protein (GFAP) promoter. Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 50 publications
0
40
0
1
Order By: Relevance
“…resting energy expenditure and the energetic cost of activity, were different between groups and were particularly altered in line 17 mice. This could suggest a defect in sympathetic tone activity, as these mice also displayed hypogonadism [18]. Resting energy expenditure is the sum of basal energy expenditure, meal-induced thermogenesis and non-shivering thermogenesis, while energy expended with activity is the intensity of the activity multiplied by its metabolic cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…resting energy expenditure and the energetic cost of activity, were different between groups and were particularly altered in line 17 mice. This could suggest a defect in sympathetic tone activity, as these mice also displayed hypogonadism [18]. Resting energy expenditure is the sum of basal energy expenditure, meal-induced thermogenesis and non-shivering thermogenesis, while energy expended with activity is the intensity of the activity multiplied by its metabolic cost.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that these IGFBP-6 transgenic mice showed a strong transgene expression in the central nervous system, associated with a 25% decrease in cerebellum size and a 50% decrease in cerebellum GFAP expression [18].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, IGFBP-6 inhibits programmed cell death in non-small cell lung cancer cells . Overexpression of IGFBP-6 inhibits both neuroblastoma growth in vivo (Bienvenu et al, 2004) and proliferation of human bronchial epithelial cells . Therefore, IGFBP-6 exerts differential effects on the regulation of cell metabolism in different cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Although an effect on prostate development was not specifically noted, there was a generalized decrease in organ size (DeChiara et al, 1990). Similarly, transgenic mice overexpressing human Igfbp-6 under the control of the GFAP promoter show a significant decrease in body weight (Bienvenu et al, 2004).…”
Section: Discussionmentioning
confidence: 98%